Africander, Tswana and Tuli cattle of Southern Africa: Breed characterization separates fact from fiction - Trail, J.C.M. (Westview Press, Inc., 1984)
Compares the productivity of Africander, Tswana and Tuli cattle using indices calculated from data on reproductive performance, viability and growth; also evaluates the crossbreeding potentials of the Tswana breed.